History of Newmont's gold treatment facilities at Carlin operations - Arthur, B.; Dunne, Robert (Society for Mining, Metallurgy and Exploration, Inc, 2012)
Newmont Mining Corp. has been producing gold from the Carlin Trend for more than 45 years. Naturally, the focus, scale and complexity of the operations have changed considerably during this time. Newmont discovered and developed the Carlin Main orebody that is located about 32 km (20 miles) north of Carlin, NV. The property was developed as a one-mine, one-gold mill treatment plant operation, which produced about 6.2 t/a (200,000 oz/year) of doré gold bars.